FENOMENA PERLUASAN DAN PENYEMPITAN MAKNA DALAM ILMU SEMANTIK - Ahmad Sirfi Fatoni (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
This article examines the expansion and narrowing of meaning in the field of semanticsThe reasons that triggers this research because the meaning in one period of time can change and most likely different at other times, this situation occurs because of the development of thinking of language users and cultural changes. From there emerged several phenomena such as the expansion and narrowing of meaning. This research is a qualitative research. As for the research method used descriptive analysis and critical. The findings of the research are: (1) The expansion of meaning is certainly closely related to language use. The language-speaking community in expanding the meaning contained in a word can use analogy or with self-help language itself. Expansion is often caused by social factors. A word that changes its usage from a limited circle into general usage sometimes will expand its meaning and lose some of its distinguishing elements, (2) The expansion of meaning is not only a booster in the development of semantics and method in the development of linguistic science, but on the other side it shows the weakness of a language, especially for common people, (3) The expansion of meaning is the result of the abortion of some the distinguishing features of a word, while the narrowing of meaning is the result of the addition of some the distinguishing features of a word, (4) Narrowing of meaning is found in the realm of scientific and artistic terms, in fact it’s closely related to the phenomena of homonym and polysemy.